Developmental changes in the balance of glycolytic ATP production and oxidative phosphorylation in ventricular cells: A simulation study. (21st April 2017) - Sano, Hitomi I.; Toki, Tamami; Naito, Yasuhiro; Tomita, Masaru
Abstract: The developmental program of the heart requires accurate regulation to ensure continuous circulation and simultaneous cardiac morphogenesis, because any functional abnormalities may progress to congenital heart malformation. Notably, energy metabolism in fetal ventricular cells is regulated in a manner that differs from adult ventricular cells: fetal cardiomyocytes generally have immature mitochondria and fetal ventricular cells show greater dependence on glycolytic ATP production. However, although various characteristics of energy metabolism in fetal ventricular cells have been reported, to our knowledge, a quantitative description of the contributions of these factors to fetal ventricular cell functions has not yet been established. Here, we constructed a mathematical model to integrate various characteristics of fetal ventricular cells and predicted the contribution of each characteristic to the maintenance of intracellular ATP concentration and sarcomere contraction under anoxic conditions. Our simulation results demonstrated that higher glycogen content, higher hexokinase activity, and lower creatine concentration helped prolong the time for which ventricular cell contraction was maintained under anoxic conditions. The integrated model also enabled us to quantitatively assess the contributions of factors related to energy metabolism in ventricular cells. Because fetal cardiomyocytes exhibit similar energy metabolic profiles to stem cell-derived cardiomyocytes and those in the failing heart, an improved understanding of these fetal ventricular cells will contribute to a better comprehension of the processes in stem cell-derived cardiomyocytes or under pathological conditions. Highlights: Metabolism differs between adult vs fetal, stem cell, and pathologic cardiomyocytes. We present a mathematical model integrating energy metabolism characteristics. High glycogen prolonged fetal ventricular cell contraction maintenance under anoxia. Fetal factors only prolonged maintenance with low mitochondria to cytoplasm ratio. This is the first quantitative description of factor roles in fetal cell function.